New quasi uniformly accelerated motion with hidden quasi momentum - Korpinar, Zeliha; İnç, Mustafa; Korpinar, Talat; Hussain, Majid; Baleanu, Dumitru; Almohsen, Bandar (Shanghai Jiaotong University, 2022)
We firstly characterize uniformly quasi accelerated motion (UQAM) with Fermi Walker derivation. We obtain new energy of quasi tangent magnetic biharmonic particle and Lorentz field. Thus, we give new relationship between Fermi Walker parallelism and uniformly quasi accelerated motion in Heisenberg group. Moreover, we give applied geometric characterization for a uniformly quasi accelerated motion of velocity magnetic biharmonic particles in Heisenberg space. © 2022
Keywords: Biharmonic particle; Electrical energy; Heisenberg space; Magnetic field; Magnetic flux density; Quasi plasma